Jewish refugees from Germany and Austria in the British Army, 1939-45 - Kern, Steven (2004)
This thesis fills a significant gap in secondary literature on the role of Jewish refugee soldiers from Germany and Austria, who served in the British army during the Second World War, 1939-45. It goes further than any previous specialised works in this area by examining the social issues surrounding the refugee soldier's experiences in the army, such as their relationship with British soldiers and their personal attitudes towards the policies of the War Office.